In the eye of the beholder: Examining the role of dynamic capabilities, industry dynamics, and internal knowledge sharing in strategists' entry decisions - Nicole Schulte-Kulkmann (Junior Management Science (JUMS), 2024)
Dynamic capabilities are a major driver of strategic entry into new industries. Building on the dynamic capabilities approach and on strategy literature, I develop a model for strategists' assessment of entry. I examine two specific dynamic capabilities, namely absorptive capacity and new product development capability and argue that both positively influence strategists' perceived attractiveness of entering a new industry. Further, I aim to respond to the call to consider the moderating effects of both external and internal conditions, by integrating environmental dynamism and internal knowledge sharing as moderators in my model. I test my hypotheses via a conjoint experiment and data on 1,664 entry assessments embedded within 52 strategists. As expected, I find that both high levels of perceived absorptive capacity and new product development capability increase entry attractiveness. Moreover, those effects are particularly strong when the environmental dynamism in the new industry is expected to be low. Internal knowledge sharing strengthens the relationship between perceived new product development and entry attractiveness. Regarding perceived absorptive capacity, I do not find significant interactions.
Keywords: 650; absorptive capacity; dynamic capabilities; entry assessment; new product development; strategic entry